The simple physics of the bending magnet spectrum. (29th May 2018) - Margaritondo, Giorgio
Abstract : The Doppler effect and its dependence on direction explain key spectral features of the emission of bending magnets in synchrotron sources. Abstract : A new elementary model of the bending magnet synchrotron radiation is presented, with minimal mathematical formalism. The model explains features not justified by other simplified approaches; in particular, it brings to light the key role of the directional Doppler effect.